Clinical and Ultrasonic Risk Factors for Lateral Lymph Node Metastasis in Papillary Thyroid Microcarcinoma: A Systematic Review and Meta-Analysis - Xue, Shuai; Han, Zhe; Lu, Qiyu; Wang, Peisong; Chen, Guang (Frontiers in Oncology, 2020)
Abstract: Background: Clinical and ultrasonic risk factors for lateral lymph node metastasis (LLNM) in papillary thyroid microcarcinoma (PTMC) are not well defined. Herein, A systematic review and meta-analysis were conducted to investigate clinicopathologic and ultrasonic risk features for LLNM in PTMC. Methods: A systematic search of electronic databases (PubMed, Embase, Cochrane Library, and Web of Science) for studies published until April 2019 was performed. Case–control studies and randomized controlled trials that studied clinical and ultrasonic risk factors of LLNM in PTMC were included. Results: Fourteen studies (all retrospective studies) involving 43750 patients met final inclusion criteria. From the pooled analyses, younger age<45 (OR, 1.55; 95% CI, 1.16-2.07; P =0.003), male patients (OR, 1.94; 95% CI, 1.55-2.42; P <0.00), extrathyroidal extension (OR, 3.63; 95% CI, 2.28-5.77; P <0.00), tumor multifocality (OR, 2.24; 95% CI, 1.53-3.28; P <0.00), tumor > 0.5cm. (OR, 2.24; 95% CI, 1.53-3.28; P <0.00), central lymph node metastasis (OR, 5.61; 95% CI, 4.64-6.79; P <0.00), >25% tumor contact with thyroid capsule (OR, 6.66; 95% CI, 1.96-22.65; P =0.002), tumor calcification (OR, 2.90; 95% CI, 1.71-4.93; P <0.00), upper tumor (OR, 3.18; 95% CI, 2.23-4.55; P <0.00) were significantly associated with increased risk of LLNM in PTMC, while Hashimoto’s thyroiditis and other ultrasonic features (solid tumor, hypoechoic tumor, smooth margin and taller than wide tumor) were not significantly associated with LLNM in PTMC. Conclusions: Our analysis identified several clinicopathologic and ultrasonic factors associated with LLNM in PTMC. This finding highlights the need for a cautious and frequent postoperative surveillance of the lateral neck in high-risk PTMC patients. Moreover, high-risk ultrasonic features also need to be considered during selection of PTMC for active surveillance.